Dinâmica do uso do solo e cobertura vegetal da Ibiapaba, uma área prioritária para conservação da caatinga, e seu entorno entre os anos de 2005 à 2020 - Lima, Sâmila Silva (2022)
The human action became the main force responsible for general environmental degradation in different ecosystem types. Due to a human population growth and technology development the human species has transformed the environment faster than it can regenerate. Dry forests are among the most threatened ecosystems, which includes the Caatinga dry forests of North- eastern Brazil. Inside Caatinga ecosystem the Ibiapaba region has been considered as priority area for conservation and has facing land use changes in the past years due to human pressures as urbanization, agriculture and cattle raising. These changes has been intensified with new land uses as wind power plants, which has affected the landscape and increased the fragmentation of vegetation cover. Fragmentation and habitat loss are among the most aggressive human impacts and has progressively amplified among Caatinga, especially in Ibiapaba region. In face of that, this research aims to map different land use as well as measure the vegetation cover loss at different vegetation types localized on the Ibiapaba Glint in the last 15 years. The land use and land cover mapping was made with satellites images with supervised classification using Random Forest method applied on Google Earth Engine platform. This methodology allowed producing comparative maps for land use in the years 2005, 2007, 2011, 2014, 2017, and 2020 as well as a table result which shows changes on vegetation cover at Ibiapaba region. Among Ibiapaba and its surroundings, crystalline Caatinga has 3,913 Km2, sedimentary Caatinga approximately 15,000 Km2, wet forest 1,522 Km2, and dry forests 1,370 Km2. In addition, for 2020 year 64% of Ibiapaba area and its surroundings has natural vegetation and 36% of its remained area are identified as being under human use, agriculture, or exposed soil.